Aislamiento de microorganismos para control biológico de moniliophthora roreri (2013)
Moniliophlhora roreri is the causal agent of cocoa Moniliasis, which produces losses of up to 60% of the crop, as it affects only its commercial product, the cob. Biological control appears as an alternative management, using endophytic microorganisms. The reason because of this research came up was that it was aimed to isolate microorganisms with antagonist potential for biological control towards the phytopathogen M. roreri in Norte de Santander. This is done through isolation and identiﬁcation of the phytopathogen using disinfection protocols and potential antagonists to it, with serial dilutions sows, microbial genera selection with the highest antagonist potential, and the evaluation of these through a dual plate to assess the biocontrol fungi effect and antibiosis for bacteria evaluation. We took samplesin the municipalities of Cucuta, Sardinata, El Tarra, Tibu and El Zulia. As a result, we succeeded in isolating 17 phytopathogen strains and 20 strains (14 fungi and 6 bacteria). Of these strains, we chose 4 fungi strains and 3 bacteria. When we assessed the fungi and bacteria’s antagonistic capacity associated with cocoa against M. roreri, we obtained that the best PICR was Tl with an average of 80.72%, followed by T2 with 72.45%. This demonstrated that Paecilomyoes sp. fungus presents the most inhibitory effect in vitro. Finally, we found that the Bacillus brevis (B2005) strain was the most effective, with values higher than 89% for the bacterial isolates antibiosis evaluation.